(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Cold powder is a traditional cosmetic made from natural ingredients that is still widely used; however, formulation development and quality evaluation, particularly microbiological aspects, require further attention. This study aimed to formulate and evaluate the quality of cold powder containing Erythrina subumbrans leaf extract, including physical quality and microbiological tests. This study used an experimental method with four formulations, namely F0 (0%), F1 (3%), F2 (6%) and F3 (9%) extract concentrations. Physical quality evaluation included organoleptic testing, homogeneity, pH, moisture content, stability, adhesion, and hedonic testing, while microbiological testing was performed through Total Plate Count (TPC) and Yeast and Mold Count (YMC). The results showed that all formulations exhibited different physical characteristics. The pH values were within the acceptable range for topical preparations, while the moisture content test indicated that F3 exceeded the permissible limit. All formulations did not meet the requirements for homogeneity and adhesion. The hedonic test showed that formulation F2 (6%) had the highest acceptance level. Microbiological testing revealed that all formulations exceeded the acceptable limits for TPC and YMC, indicating that they did not meet the safety requirements according to BPOM standards. In conclusion, cold powder containing Erythrina subumbrans leaf extract was successfully formulated; however, not all formulations met the physical quality and microbiological safety requirements. Formulation F2 showed the most potential for further development with improvements in quality and safety aspects